Desenvolvimento de lipossomas vetorizados ao receptor folato contendo paclitaxel e imatinibe coencapsulados: avaliação da atividade antiproliferativa e da expressão gênica do VEGF em células tumorais - Peres Filho, Marco Júnio (2014)
The impact of Nanotechnology is constantly raising in different areas of science, with the development of new products that bring benefits in comparison with the alternatives available in the market. When encapsulated in nanoparticles, anticancer drugs can achieve several advantages, most importantly the possibility of reducing the amount of drug administered through targeting strategies, which are not accomplished by conventional medication. Passive targeting is related to leaky vasculature in pathological sites, and active targeting comprehends the attachment of specific ligands, anchored in nanoparticles surface, to recognize and bind receptors overexpressed in cancer cells. Coencapsulation of anticancer drugs in the same pharmaceutical carrier can coordinate pharmacokinetics of encapsulated drugs. In the present work, liposomal formulations targeted to folate receptor with paclitaxel (PTX) and imatinib (IB) coencapsulated were obtained, aiming to combine cytotoxic and antiangiogenic effects of the drugs, respectively. New analytical method was developed and validated for simultaneous quantification of IB and PTX. Soy phosphatidylcholine liposomes were prepared, with cholesterol and DSPEmPEG( 2000), to obtain long circulation particles. DSPE-PEG(2000)-FA was obtained by an unpublished method of synthesis, and this product was further used in the formulation by post-insertion technique. Cytotoxic effect and VEGF gene suppression were studied in vitro in two different cell lines, MCF7 (breast adenocarcnioma) and PC3 (prostatic adenocarcinoma), after treatment with liposomal vesicles. Analytical procedures were developed with isocratic elution, 6,5 minutes runs, with linearity, specificity, precision and accuracy. Quantification limit was 750 Ng/mL and 1000 Ng/mL for IB and PTX, respectively. After extrusion, liposomes had mean diameter close to 100 nm and low polidispersion index. Post-insertion of folic acid attached to lipid anchor procedure increased polidispersion, because the procedure lasted 24h. Drug to lipid ratios were 1:26 and 1:27 (IB and PTX respectively). Lyophilized formulations containing trehalose remained stable after 60 days of storage in terms of %EE. Synthesis of DSPE-PEG(2000)-FA was confirmed by RMN, FT-IR and ESIMS techniques. Liposomal PTX was more cytotoxic (p<0,05) than free drug in MCF7 cell line, after both 24h and 48h of exposion, for all tested concentrations. Targeted formulation containing folic acid ligand, had more impact on cell viability reduction (p<0,05) than non targeted liposomes (LPIP), also after 24h. On PC3 cell line cell viability reduction was greater (p<0,01) when the cells were exposed to targeted vesicles loaded with 1 and 10 Ng/mL of IB and PTX, after 24 and 48h. VEGF gene expression was reduced in MCF7 and PC3 (p<0,05), and once more targeted vesicles showed better results than non-targeted liposomes. It is, thus, plausible to conclude, through in vitro experiments results, that the attachment of folic acid to liposomal formulations, resulting in multi-functional liposomes, is an interesting strategy to achieve enhanced internalization and accumulation of drugs in targeted cells. This was observed by the enhancement of cytotoxic and antiangiogenic effects in breast and prostate cell lines.